Cytostatic/Cytotoxic Effects of 5‐Fluorouridine Nucleolipids on Colon, Hepatocellular, and Renal Carcinoma Cells: in vitro Identification of a Potential Cytotoxic Multi‐Anticancer Drug. Issue 3 (March 2014) - Farhat, Anisa; Malecki, Edith; Bonaterra, Gabriel A.; Röthlein, Doris; Wolf, Martin; Schmitt, Jürgen; Rosemeyer, Helmut; Kinscherf, Ralf
Abstract The insufficient penetration through the cell membranes is one of the major drawbacks of chemotherapeutics such as 5‐fluorouracil (5‐FU; 1). To improve the penetration, a useful strategy is the attachment of lipophilic moieties. Thus, we have synthesized a series of nucleolipid derivatives of 5‐fluorouridine (5‐FUrd; 2a), carrying lipophilic moieties at N(3) and/or at the 2′, 3′‐O position, i.e., 3a, 3b, 4–7, and tested their cytostatic/cytotoxic activities towards three carcinoma cell lines (colon (HT‐29), hepatocellular (HepG2), and renal (RENCA)) in comparison with 5‐FU (1) and 5‐FUrd (2a). After 48 h of incubation, four derivatives, 3a, 3b, 5, and 7, showed inhibitory effects on the survival of HT‐29, HepG2, and RENCA cells. Additionally, to differentiate between anticancer and side‐effects, we tested the cytotoxicity of the derivatives in human macrophages. Interestingly, the derivatives 4, 5, and 6 did not exhibit any effects on survival of THP‐1 macrophages. Furthermore, we investigated the apoptosis induction of compound 1 and 2a, and the above‐mentioned derivatives in HT‐29 cells. Derivative 5 showed the highest significant (p<0.05; p<0.01) increase of the apoptosis at 80 μM after 2‐h or 4‐h treatment, as well as after 6‐h incubation at 40 μM (p<0.05). Real‐time PCR revealed that 40‐μM derivative 5 showed a 1.8‐fold increase of the pro‐apoptotic caspase‐3 gene and a twofold significant increase (p<0.01 and p<0.05 vs. control and 1, resp.) of the tumor suppressor TP53 gene, whereas the other compounds did not show any effect. We demonstrated that some 5‐FUrd derivatives such as compound 5 are more effective than 5‐FU or 5‐FUrd concerning a cytotoxic (vs. cytostatic (5‐FU, 5‐FUrd)) effect on different cancer cell lines, but without cytotoxic side‐effects on differentiated macrophages. Thus, compound 5 is suggested as a novel potent cytotoxic multi‐anti‐cancer drug.